Reading component skills in dyslexia: word recognition, comprehension and processing speed - de Oliveira, Darlene G.; da Silva, Patrícia B.; Dias, Natália M.; Seabra, Alessandra G.; Macedo, Elizeu C. (Frontiers in Psychology, 2014)
The cognitive model of reading comprehension posits that reading comprehension is a result of the interaction between decoding and linguistic comprehension. Recently, the notion of decoding skill was expanded to include word recognition. In addition, some studies suggest that other skills could be integrated into this model, like processing speed, and have consistently indicated that this skill influences and is an important predictor of the main components of the model, such as vocabulary for comprehension and phonological awareness of word recognition. The following study evaluated the components of the reading comprehension model and predictive skills in children and adolescents with dyslexia. 40 children and adolescents (8-13 years) were divided in a Dyslexic Group (DG, 18 children, MA = 10.78, SD = 1.66) and Control Group (CG 22 children, MA = 10.59, SD = 1.86). All were students from the 2nd to 8th grade of elementary school and groups were equivalent in school grade, age, gender, and IQ. Oral and reading comprehension, word recognition, processing speed, picture naming, receptive vocabulary and phonological awareness were assessed. There were no group differences regarding the accuracy in oral and reading comprehension, phonological awareness, naming, and vocabulary scores. DG performed worse than the CG in word recognition (general score and orthographic confusion items) and were slower in naming. Results corroborated the literature regarding word recognition and processing speed deficits in dyslexia. However, dyslexics can achieve normal scores on reading comprehension test. Data supports the importance of delimitation of different reading strategies embedded in the word recognition component. The role of processing speed in reading problems remain unclear.